2018
DOI: 10.1097/igc.0000000000001141
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Protein Signature Predicting Clinical Outcome in High-Grade Serous Ovarian Cancer

Abstract: CXCL11 combined with HMGA2 signature was a clinically applicable prognostic model that could precisely predict an HGSOC patient's OS and tumor recurrence. This model could serve as an important tool for risk assessment of HGSOC prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…25,26 Protein signatures in ovarian cancer have been proposed as serum biomarkers, as well as to predict prognosis and chemosensitivity. [27][28][29] Similar biomarker and prognostic markers have been proposed in lung cancer and breast cancer. [30][31][32] Additional investigation into protein signatures in PDAC can provide similar utility in prognosis and chemosensitivity and deserves consideration.…”
Section: Discussionmentioning
confidence: 89%
“…25,26 Protein signatures in ovarian cancer have been proposed as serum biomarkers, as well as to predict prognosis and chemosensitivity. [27][28][29] Similar biomarker and prognostic markers have been proposed in lung cancer and breast cancer. [30][31][32] Additional investigation into protein signatures in PDAC can provide similar utility in prognosis and chemosensitivity and deserves consideration.…”
Section: Discussionmentioning
confidence: 89%
“…CXCL11 levels were also correlated with the stroma signature in the mesenchymal and differentiated subtypes, supporting a more context‐dependent role of CXCL11. In line with such role, CXCL11 has recently been identified as a predictive marker for OC clinical outcome (Jin et al ., ). In addition, when analyzed in the mesenchymal subtype, both CXCR7 and CXCL11 strongly correlate with genes associated with ECM and OC invasion phenotype.…”
Section: Discussionmentioning
confidence: 97%
“…It was also reported that its downregulation can inhibit tumor angiogenesis in epithelial OV (38). High CXCL11 expression was determined to predict worse OS in high-grade serous OV (39). STAT4 (signal transducer and activator of transcription 4) is a member of the STAT family.…”
Section: Discussionmentioning
confidence: 99%